La defensa del medioambiente y la construcción de ciudadanía: reflexiones en torno a un “movimiento ciudadano” en la ciudad de Valdivia, Chile - Bárbara Morales Aguirre (Les Cahiers ALHIM)
From an anthropological approach, this article seeks to explore the process of citizenship building that holds the movement “Action for the swans” in the context of the defense of their local environment. Delving into the collective experience of the members of the movement, we will analyze the different conceptions of citizenship that are at stake, as well as the principles, rights and practices that they found within their own area of participation. Well will also show the way the movement questions and redefines dominant notions of citizenship, policies, participation, among others, which are the basis of the political project of the current Chile.